Regnum Francie: A Problem in Capetian Administrative Usage - Wood, Charles T. (Traditio, 1967)
No one reading Suger's life of Louis VI would be apt to think that the abbot of Saint Denis had an extremely broad or, as one used to say, ‘liberal’ conception of the territorial limits of Francia. On the contrary, it is evident that for him Francia was a compact unit of lands roughly equivalent to the more modern Ǐle de France, lands which in no way approximate what France was later to become. One finds, for example, that Louis after his various provincial expeditions is described as returning ‘in Franciam,’ be it from Flanders, Auvergne, or Berry. Similarly, frontiers and marches are to be found facing not only the empire, which is natural enough, but also Normandy, Berry, Auvergne, and Burgundy. In short, for Suger Francia was hemmed in by a host of other and often hostile lands, and while the king's duty might be to control them as best he might, it is nevertheless apparent that they do not, in Suger's normal use of the term, constitute part of Francia.